2002
DOI: 10.1124/jpet.102.044644
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine A1Receptor AgonistN6-Cyclopentyladenosine Affects the Inactivation of Acetylcholinesterase in Blood and Brain by Sarin

Abstract: The objective of the present study was to develop a kinetics of pharmacodynamics model to properly describe and investigate the in vivo interaction between the selective adenosine A 1 agonist N 6 -cyclopentyladenosine (CPA), acetylcholinesterase (AChE) in blood and brain, and the AChE-inhibitor sarin (isopropylmethylphosphonofluoridate). The direct interaction of CPA (2 M) on the inhibition of AChE by sarin was studied in vitro in heparinized rat blood and in 10% (w/v) brain homogenate. CPA did not directly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…The inhibition levels in these two animals were *90 and 95%, in striate body and brain, respectively, compared to 75 and 90%, in animals that did not have seizures on their EEG. These high levels of central AChE inhibition, expected to be a requirement for seizure development, are in line with previous studies [21][22][23]. Other workers have shown in guinea pigs, using a different route of administration, that of all nerve agents tested, VX was least likely to produce seizure activity in all animals [24,25].…”
Section: Discussionsupporting
confidence: 84%
“…The inhibition levels in these two animals were *90 and 95%, in striate body and brain, respectively, compared to 75 and 90%, in animals that did not have seizures on their EEG. These high levels of central AChE inhibition, expected to be a requirement for seizure development, are in line with previous studies [21][22][23]. Other workers have shown in guinea pigs, using a different route of administration, that of all nerve agents tested, VX was least likely to produce seizure activity in all animals [24,25].…”
Section: Discussionsupporting
confidence: 84%
“…It was shown previously that AChE activity in blood is a bad predictor for cholinergic clinical signs due to acute OP poisoning (Bueters et al 2003). Logistic regression analysis of the present results, using lower doses of OP compared to that study, revealed the inhibition of AChE in blood to be a good predictor for the probability of chewing, shivering, seizures, convulsions and tremor, but not for respiratory distress and death (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The decline of therapeutic efficacy at higher doses of obidoxime might be ascribed to the inhibitory actions that phosphonylated obidoxime exerts on AChE (Harvey et al 1986; van Helden et al 1994). The slight delay of complete inhibition of AChE in the blood and probably also in the brain by obidoxime might explain its therapeutic efficacy, as only little amounts of active AChE in the brain are sufficient to improve the aforementioned parameters (Bueters et al 2003). In addition, suspected direct pharmacological actions of obidoxime might facilitate adaptive processes (van Helden et al 1994, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…These samples were stored at Ϫ70°C until analysis. Thawed samples were appropriately diluted and were assayed in quadruplicate for AChE activity using a 96-well microplate modification of the Ellman method (Bueters et al, 2003). Ethopropazine (10 M) was used as a specific inhibitor of butyrylcholinesterase.…”
Section: Methodsmentioning
confidence: 99%